(untitled) (Journal of Environmental Science and Natural Resources, 2012)
Noise pollution is one of the most harmful pollution. Uncontrolled noise of Dhaka city has made a serious and vulnerable situation for the dwellers. Mixed areas are used in multidimensional ways so the degree and intensity of noise pollution is often higher. In this regard, this study has been framed to explore the nature and vulnerability of noise pollution in mixed areas as well as to realize its impacts using GIS approach. Accordingly, an investigation has been carried out employing different field techniques in Ramna area which is a mixed area in nature and important part of the city. This study put an effort to determine the level of noise pollution and its zone of influence to know how far noise is affecting the socio-environment of the study area. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11548 J. Environ. Sci. & Natural Resources, 5(1): 09-17, 2012